NUMERICAL SOLUTION OF ABSORBING BOUNDARY CONDITIONS ON TWO DIMENSIONAL ACOUSTIC WAVE - Mohammad Mahfuzh Shiddiq (Mathematics Study Program, Faculty of Mathematics and Natural Sciences, Lambung Mangkurat, 2013)
In this paper will be determined numerical solution of two-dimensionalacoustic wave equation with absorbing boundary conditions that obtained at Siddiq [9].Method used is determine nite dierence equation in two-dimensional acoustic wavepropagation problems satised absorbing boundary conditions.